Effective exploitation of a geyser bubble-chamber equipment as a background-free fast neutron detector - R. Bertoni (SpringerOpen, 2021)
Abstract The MOSCAB equipment, a geyser-concept bubble-chamber originally thought for the search of dark matter in the form of WIMPs, is employed for the detection of fast neutrons. Once the background-free operating conditions are determined such that the detector is sensitive only to neutrons, which occurs when the neutron energy threshold required for nucleation is higher than approximately 2.5 MeV, the detector response to fast neutrons is investigated using a $${^{241}}$$ 241 AmBe neutron source. Sets of detection efficiency functions are then produced via Monte Carlo simulations and post-processing, their validation being performed experimentally and discussed. Finally, the use of the detector to measure the fast neutron activity of very weak n-sources in low neutron background environments, as well as to monitor the cosmic ray variations through the neutron component of the Extensive Air Showers, is considered.